THE IMPACT OF GREEN MARKETING ON PURCHASE INTENTION OF NATURAL BEAUTY PRODUCTS FROM MSMEs IN INDONESIA - Markhamah, Siti; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to analyze the impact of green marketing on consumer purchase intentions on green products offered by Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The implementation of green marketing strategies is increasingly relevant in the context of increasing consumer awareness of environmental issues and the importance of sustainability. However, there are challenges for MSMEs in adopting green marketing, including high implementation costs and low levels of consumer awareness. This study uses a quantitative approach with a survey method involving a number of MSME green product consumer respondents in Indonesia. As public awareness of environmental issues increases, consumers are increasingly choosing environmentally friendly and sustainable products. The research method used is a survey with a questionnaire distributed to consumers who have experience buying natural beauty products. The collected data were analyzed using descriptive statistics and regression techniques to identify the relationship between green marketing strategies-including environmental communication, product labeling, and brand image-with purchase intention. The results show that green marketing significantly influences purchase intention, where consumers are more likely to choose products from MSMEs that implement environmentally friendly practices. The findings provide important implications for MSMEs in formulating effective marketing strategies to attract the attention of consumers who are increasingly concerned about sustainability